2020
DOI: 10.1016/j.corsci.2019.108391
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrogen on the early stages of oxidation of a magnesium alloy

Abstract: The early stage oxidation of germanium-doped magnesium alloys was investigated via atom probe tomography. A catalytic reaction cell attached to a local electrode atom probe was used for controlled exposure of electropolished specimens to oxygen gas. Hydrogen was detected in certain samples, thought to be introduced during electropolishing. A preferential interaction/reaction between oxygen and hydrogen was found in samples containing hydrogen-rich regions prior to oxidation. These results suggest that hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Recent developments in APM offer promise for investigating the complex composition and structure changes accompanying gas/surface interactions. The in situ reactor, for APT analysis first described by others [6,[36][37][38][39] and more Fig. 9 Variations of the composition in Co n+ , Co 2 O n+ , CoO n+ , O n+ and O 2 n+ species detected (at% on the left scale and the O:Co ratio on the right scale) as a function of the static voltages (V stat ) and pulse frequencies applied broadly for APM analysis reported here and elsewhere [5], provides a new pathway for understanding atomic-scale processes involved in gas/surface reactions in a wide range of material systems, from single crystals of pure metals like Rh, to more complex alloys such as zirconium alloys.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent developments in APM offer promise for investigating the complex composition and structure changes accompanying gas/surface interactions. The in situ reactor, for APT analysis first described by others [6,[36][37][38][39] and more Fig. 9 Variations of the composition in Co n+ , Co 2 O n+ , CoO n+ , O n+ and O 2 n+ species detected (at% on the left scale and the O:Co ratio on the right scale) as a function of the static voltages (V stat ) and pulse frequencies applied broadly for APM analysis reported here and elsewhere [5], provides a new pathway for understanding atomic-scale processes involved in gas/surface reactions in a wide range of material systems, from single crystals of pure metals like Rh, to more complex alloys such as zirconium alloys.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to experimentally control the ambient reaction conditions relevant to an atomic to nanoscale understanding of oxidation or catalysis on a metal or metal alloy surface is enabled by a reactor connected to an atom probe instrument. The design, fabrication, and demonstration of a gasphase reactor attached to an atom probe has been previously reported by Bagot and Visart de Bocarmé et al, and was demonstrated to explore reactive gas interactions on bimetallic metal systems: H 2 /Pd [36], O 2 /Mg alloy [36,37], NO/ PtRh [38], O 2 /PtRh [6] and O 2 /AuAg [39]. They reported local chemical segregation within the bulk and on material surfaces such as Ag-and Rh-enriched surface layers induced by O 2 exposure of AuAg and PtRh respectively, or Rh depletion caused by NO adsorption on PtRh.…”
Section: Design and Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…The recently developed reaction chambers attached to the vacuum systems of APT instruments have been used to study composition changes of oxide layers. These chambers have demonstrated their usefulness in analysing near-surface compositional changes during oxidation of catalyst materials such as Pt-Rh, Pt-Ru, Pt-Ru-Rh, Pd-Rh, and Rh 5,6,37 and Mg alloys 38 .…”
Section: Introductionmentioning
confidence: 99%